Dielectric functions of In-1 (-) xAlxSb alloys for arbitrary compositions with parametric modeling - Diware, Mangesh S.; Kim, Tae Jung; Yoon, Jae Jin; Barange, Nilesh S.; Byun, Jun Seok; Park, Han Gyeol; Kim, Young Dong; Shin, Sang Hoon; Song, Jin Dong (ELSEVIER SCIENCE SA, 2013)
By determining the parameters of the parametric model (PM) for selected Al compositions x of In-1 (-) xAlxSb, we provide the information needed to accurately calculate the room-temperature dielectric functions epsilon = epsilon(1) + i epsilon(2) of these alloys from 1.5 to 6.0 eV as a continuous function of x over the entire composition range 0 <= x <= 1. Our parameters are determined from data obtained by spectroscopic ellipsometry for Al compositions x = 0.00, 0.142, 0.341, 0.539, 0.754, and 1.00. The PM dielectric functions are found to be in excellent agreement with the data. These results will be useful in many aspects of research and technology. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: ELECTRON-MOBILITY TRANSISTORS; V COMPOUND SEMICONDUCTORS; FILMS; INAS; GAAS; INSB; INP; GE; SI